Effects of highland environments on clonal diversity in aquatic plants: An interspecific comparison study on the Qinghai-Tibetan Plateau - Wu, Zhigang; Wang, Zhong; Xie, Dong; Wang, Huijun; Zhao, Aiwen; Wang, Yalin; Wang, Hanling; Xu, Xinwei; Li, Tao; Zhao, Jindong (Frontiers in Plant Science, 2022)
Clonal reproduction is one of the most distinctive characteristics of plants and is common and diverse in aquatic macrophytes. The balance between sexual and asexual reproduction is affected by various conditions, especially adverse environments. However, we know little about clonal diversity of aquatic plants under suboptimal conditions, such as at high altitudes, and having this information would help us understand how environmental gradients influence patterns of clonal and genetic variation in freshwater species. The microsatellite data of four aquatic taxa in our previous studies were revisited to estimate clonal and genetic diversity on the Qinghai-Tibetan Plateau. Clonal diversity among different genetic groups was compared. Local environmental features were surveyed. Beta regressions were used to identify the environmental factors that significantly explained clonal diversity for relative taxon. The level of clonal diversity from high to low was Stuckenia filiformis > Hippuris vulgaris > Myriophyllum species > Ranunculus section Batrachium species. A positive correlation between clonal and genetic diversity was identified for all taxa, except H. vulgaris. Clonal diversity was affected by climate in S. filiformis and by the local environment in H. vulgaris. For Myriophyllum spp., low elevation and high sediment nutrition were significant for sexual recruitment. The environmental effects on clonal diversity were not significant in R. sect. Batrachium spp. Clonal diversity of aquatic plants is moderate to high and varies greatly in highlands. The effects of breeding systems and environmental factors on the patterns of clonal variation were identified. Elevational gradients, climates and local conditions play different roles in clonal diversity among relative taxon. Our results highlight the importance of sexual recruitment in alpine aquatic plant populations and the influence of environmental factors on the genetic patterns in freshwater species at local and regional scales.